INTERNATIONAL EXPERIENCE IN THE FORMATION AND MANAGEMENT OF COMMERCIAL BANKS' CAPITAL - Tozhaboeva Nilufar (Western European Studies, 2024)
This article examines the international experience of formation and management of commercial banks’ capital on the example of several developed foreign countries. The requirements of the Basel Committee on capital formation and management are also considered. The analysis compares the practice of foreign countries in matters of formation and management of capital with the practice of the Republic of Uzbekistan. As a result, it was revealed that despite the application of the Basel Recommendations by most countries, there are still differences, which is explained by the level of development and market conditions of each country. Based on the results of studying and analyzing international experience in the formation and management of capital of commercial banks, relevant conclusions and some proposals were developed
Keywords: management; conclusions; Uzbekistan; developed